2022
DOI: 10.1016/j.gim.2021.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and investigation of the role of genetic variation in phenotypic variability and response to treatment in a large pediatric Marfan syndrome cohort

Abstract: In a large cohort of 373 pediatric patients with Marfan syndrome (MFS) with a severe cardiovascular phenotype, we explored the proportion of patients with MFS with a pathogenic FBN1 variant and analyzed whether the type/location of FBN1 variants was associated with specific clinical characteristics and response to treatment. Patients were recruited on the basis of the following criteria: aortic root z-score > 3, age 6 months to 25 years, no prior or planned surgery, and aortic root diameter < 5 cm. Methods: Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 36 publications
0
26
1
Order By: Relevance
“…This study also noticed a clear gradient in the proportion of ectopia lentis according to the location of the dominant negative FBN1 variant, with the highest prevalence of lens dislocation in the N‐terminal region (Meester et al, 2021). In contrast to the findings on aortic risk, skeletal features including pectus excavatum and tall stature are more pronounced in patients carrying haploinsufficient variants (Meester et al, 2021). Similarly, another study in adult MFS patients reported an association between premature stop codon variants and a higher risk of severe scoliosis and tall stature (Arnaud et al, 2021).…”
Section: Molecular Comparison Of the “Tall” And “Short” Fibrillin‐1/2...mentioning
confidence: 72%
See 2 more Smart Citations
“…This study also noticed a clear gradient in the proportion of ectopia lentis according to the location of the dominant negative FBN1 variant, with the highest prevalence of lens dislocation in the N‐terminal region (Meester et al, 2021). In contrast to the findings on aortic risk, skeletal features including pectus excavatum and tall stature are more pronounced in patients carrying haploinsufficient variants (Meester et al, 2021). Similarly, another study in adult MFS patients reported an association between premature stop codon variants and a higher risk of severe scoliosis and tall stature (Arnaud et al, 2021).…”
Section: Molecular Comparison Of the “Tall” And “Short” Fibrillin‐1/2...mentioning
confidence: 72%
“…However, these findings are contradicted by a recent study in a pediatric MFS cohort showing that dominant negative variants in exons 26–49 result in a more severe aortic phenotype than patients with haploinsufficient variants or dominant negative variants in other exons (Meester et al, 2021). This study also noticed a clear gradient in the proportion of ectopia lentis according to the location of the dominant negative FBN1 variant, with the highest prevalence of lens dislocation in the N‐terminal region (Meester et al, 2021). In contrast to the findings on aortic risk, skeletal features including pectus excavatum and tall stature are more pronounced in patients carrying haploinsufficient variants (Meester et al, 2021).…”
Section: Molecular Comparison Of the “Tall” And “Short” Fibrillin‐1/2...mentioning
confidence: 90%
See 1 more Smart Citation
“…Chen et al and Guo et al further proved independently that DN variants were associated with a higher degree of EL compared to the HI ones in cohorts of congenital EL ( Chen et al, 2021a ; Guo et al, 2021 ). The variants associated with EL also cluster in the N-terminus of the FBN1 gene ( Comeglio et al, 2007 ; Faivre et al, 2007 ; Baudhuin et al, 2015 ; Meester et al, 2022 ). And patients harboring variant in the neonatal region also had a higher incidence of EL ( Faivre et al, 2007 ).…”
Section: Genotype and Clinical Manifestationsmentioning
confidence: 99%
“…Most of the genotype-phenotype correlations studied a combination of skeletal features or systemic scores. Patients harboring HI variants or variants in the neonatal region often show more prominent skeletal features than those with DN ones ( Schrijver et al, 2002 ; Comeglio et al, 2007 ; Arnaud et al, 2021a ; Meester et al, 2022 ). DN (-Cys) variants were also associated with more severe skeletal manifestations than DN (+Cys) and DN (Others) ( Faivre et al, 2009b ; Arnaud et al, 2021a ).…”
Section: Genotype and Clinical Manifestationsmentioning
confidence: 99%